Comparison of Supraceliac and Infrarenal Aortic Conduits in Liver Transplantation: Is There a Difference in Patency and Postoperative Renal Dysfunction?. Issue 11 (November 2019) - Livingston, David; Lee, David D.; Croome, Sarah; Burcin Taner, C.; Croome, Kristopher P.
Abstract : Background: Aorto-hepatic conduits can provide arterial inflow for liver transplants in cases where the native hepatic artery is unsuitable for use. Methods: Clinical outcomes of all patients undergoing liver transplantation (LT) with an aorto-hepatic conduit between 2000 and 2016 were included. Recipients were divided into 2 groups: those with a supraceliac (SC) aortic conduit (N = 22) and those with an infrarenal (IR) aortic conduit (N = 82). Results: There was no difference in calculated model for end-stage liver disease score between the 2 groups. The SC group received grafts with a higher mean donor risk index (1.69 versus 1.48; P = 0.02). Early allograft dysfunction was 18.2% in the SC group and 29.3% in the IR group ( P = 0.30). In the SC group, 10.5% of patients required initiation of postoperative continuous renal replacement therapy compared to 12.1% of patients in the IR group ( P = 0.69). No difference in the rate of postoperative acute kidney injury was seen between the 2 groups ( P = 0.54). No significant difference in median creatinine at 1 year was seen between the SC (1.2 mg/dL; IQR 1–1.3) and IR (1.2 mg/dL; IQR 0.9–1.5) groups ( P = 0.85). At a median follow-up of 5.3 years, thrombosis of the aortic conduit occurred in 0% of patients in the SC group and 6.1% of patients in the IR group ( P = 0.24). Graft survival was not significantly different between the 2 groups ( P = 0.47). Conclusions: No difference in renal dysfunction as demonstrated by need for post-LT continuous renal replacement therapy, acute kidney injury, or creatinine at 1 year post-LT was seen between SC and IR aortic conduits. A slight trend of higher conduit thrombosis rate was seen with IR compared to SC aortic conduits; however, this did not reach statistical significance. Both SC and IR aortic conduits represent reasonable options when the native hepatic artery is unsuitable for use.